Assessing the Association between Clients’ Level of Satisfaction and Retention of National Health Insurance Scheme Membership in Ghana: A Study in the Greater Accra Region - Agartha Afful Boateng (Archives of Current Research International, 2022)
Introduction: Since the implementation of National Health Insurance Scheme (NHIS), fewer Ghanaians have been actively enrolled. Recently, there has been dwindling enrollment rate amongst the populace. Studies have revealed that clients’ satisfaction with services received may influence repurchasing behaviour. Aim: This study aimed at investigating the association between clients’ satisfaction with services and the intention to maintain NHIS membership. Methodology: This study was a household cross-sectional survey conducted in the Greater Accra Region. Data was gathered via distribution of 424 well-structured questionnaires amongst enrollees who were 18 years and above. Systematic random sampling was used in the selection of households and data was collected between November, 2018 and February, 2019. Client’s level of satisfaction was assessed on a Likert scale. The data was analyzed using SPSS version 23, chi-square test and Cramer’s V test. Results: The response rate for this study was 94.3% and the result revealed that 60% of the participants expressed satisfaction with NHIS services, 34.5% were neutral, and 5.5% dissatisfied with NHIS services. Few of the respondents (28.3%) expressed the intention to maintain NHIS membership. Furthermore, there was no statistical association between clients’ overall satisfaction and retention of NHIS membership (p=.24). Retention of membership with NHIS was weakly associated with satisfaction with premium (p=.01, Cramer’s V=.16), geographical accessibility of health care facilities (p=.03, Cramer’s V=.13), and healthcare provider and clients’ interpersonal relationship (p=.04, Cramer’s=.12) Conclusion: Clients’ satisfaction with NHIS services is necessary but not sufficient to influence retention of membership with the scheme. Hence, the need for health care providers to maintain good interpersonal relationship with clients, ensure geographical accessibility of NHIS accredited health care facilities, and further research of predictors to retention of NHIS membership is recommended.